The requirements management practices: A study at UUM IT - Abdulameer, Enas Fadhil (2015)
Requirements engineering is a main process in software engineering that focusing on development and managing the user requirements. One of the requirements engineering activities is requirements management. It plays an important role when it comes to the support of product development teams. Despite this, there is a lack of practice in requirements management activity in the software project development. Malaysian software markets are still facing several problems in requirements management practices such as requirements quality, requirements inadequately, and identification of requirements; with limited studies that address it. In this study, UUM IT as computer services provider in a local universities in Malaysia is design as case study, to represent as one organization in Malaysia software markets. This study aims to investigate the current situation for the requirement management in UUM IT, and assess the relationship CMMI level 2 with the requirements management practices in UUM IT. This study adopted mixed method through used questionnaire with the UUM IT team, as well as, interviews with managers of UUM IT for more reliability. The outcome of study showed that the UUM IT are used requirements management activities but there is a need for more attention and improve. Moreover, the study proposes CMMI appraisal method to enhance the performance of software development team